1985
DOI: 10.1136/gut.26.7.724
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis: a lethal disease of increasing incidence.

Abstract: SUMMARY Between 1968 and 1979 650 patients in the Bristol clinical area suffered 737 attacks of acute pancreatitis. Sex distribution was approximately equal and mean age was 60 years.Comparison with the previous decade shows an increase in mean annual incidence of first attacks from 53 8 to 73-0 cases per million population. Case mortality was unchanged at 20%. In no less than 35% of fatal cases the diagnosis was first made at necropsy. Gall stones were detected in 50% of first attacks, predominantly in women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
3
8

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(161 citation statements)
references
References 17 publications
10
140
3
8
Order By: Relevance
“…6 where the mean age was 42.4 years (range 20-69 years) whereas the study by Corfield et al have shown the mean age to be 60 years (range 3-94 years). 7 In chronic pancreatitis, the mean age of the patients were 45.4 years (range 30-69 years) which differs from the study by Balaji LN and Tandon RK where the mean age was 23.9 years. 8 In acute pancreatitis case sex ratio was 1.7:1 (25 males, 15 females).…”
Section: Resultscontrasting
confidence: 51%
“…6 where the mean age was 42.4 years (range 20-69 years) whereas the study by Corfield et al have shown the mean age to be 60 years (range 3-94 years). 7 In chronic pancreatitis, the mean age of the patients were 45.4 years (range 30-69 years) which differs from the study by Balaji LN and Tandon RK where the mean age was 23.9 years. 8 In acute pancreatitis case sex ratio was 1.7:1 (25 males, 15 females).…”
Section: Resultscontrasting
confidence: 51%
“…However, the variation of aetiology of pancreatitis is quite marked and depend on country of origin. 17 In this study most cases (60%) were idiopathic i.e. no cause is found.…”
Section: Discussionmentioning
confidence: 97%
“…4 Approximately 2 to 5% of cases of acute pancreatitis are drug-related. Drugs cause pancreatitis either by a hypersensitivity reaction or by the generation of a toxic metabolites.…”
mentioning
confidence: 99%
“…2 Gall stones and chronic ethanol abuse account for 70% of cases of acute pancreatitis. 3 Pathologically there are two types of pancreatitis, interstitial and necrotizing. 4 Pathophysiologic mechanisms include micro-circulatory injury, leucocyte chemo-attraction, release of pro and anti-inflammatory cytokines, oxidative stress, leakage of pancreatic fluid into the region of pancreas, bacterial translocation to the pancreas and systemic circulation.…”
Section: Introductionmentioning
confidence: 99%